The Influence of Social Influence, Relative Advantage, User Satisfaction on Cloud-Based E-Learning with Behavioral Intention as a Mediating Variable - Muhammad Cevin Yunior; Yvonne Augustine Sudibijo (Technium Social Sciences Journal, 2024)
This research investigates the influence of social influence, relative advantage, and user satisfaction on cloud-based e-learning adoption, with behavioral intention acting as a mediating variable. Drawing on existing literature, hypotheses are formulated to explore these relationships. The study integrates models such as DOI, TAM, and UTAUT to propose hypotheses, guided by empirical findings from Lebanon, the Philippines, and Indonesia. The hypotheses posit positive impacts of social influence (H1), relative advantage (H2), and user satisfaction (H3) on cloud-based e-learning adoption. Additionally, the study explores the mediating role of behavioral intention in the relationships between social influence (H4), relative advantage (H5), user satisfaction (H6), and cloud-based e-learning adoption. The operational model is presented, depicting the relationships among variables. The research adopts an explanatory approach, using questionnaires distributed to 143 university students engaging in cloud-based e-learning. Descriptive statistics and validity tests ensure data quality, and hypothesis testing involves Mediated Regression Analysis. Results indicate that relative advantage and user satisfaction positively impact cloud-based e-learning, while social influence’s direct impact is inconclusive. Behavioral intention does not mediate the relationships as hypothesized, highlighting the nuanced nature of cloud-based e-learning adoption. The study provides insights into the interplay of factors influencing cloud-based e-learning adoption, contributing to the understanding of technology acceptance in educational contexts.